2005
DOI: 10.1136/bmj.38343.670868.d3
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in women with early breast cancer: five year observational cohort study

Abstract: Objective To examine the prevalence of, and risk factors for, depression and anxiety in women with early breast cancer in the five years after diagnosis. Design Observational cohort study. Setting NHS breast clinic, London. Participants 222 women with early breast cancer: 170 (77%) provided complete interview data up to either five years after diagnosis or recurrence. Main outcome measures Prevalence of clinically important depression and anxiety (structured psychiatric interview with standardised diagnostic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

69
893
19
57

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,113 publications
(1,038 citation statements)
references
References 20 publications
69
893
19
57
Order By: Relevance
“…There is some evidence that after an initial rise, the prevalence of depression decreases over time following the diagnosis of breast cancer [1]. It would have been interesting to investigate the relationship between the prevalence of depression and the time since completion of treatment in this cohort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is some evidence that after an initial rise, the prevalence of depression decreases over time following the diagnosis of breast cancer [1]. It would have been interesting to investigate the relationship between the prevalence of depression and the time since completion of treatment in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, higher rates of anxiety are found where studies report cumulative incidence over the course of the disease rather than point prevalence as reported in this study. Moreover, in relation to higher rates of anxiety and depression reported in older studies, it has been suggested that a diagnosis of breast cancer may be less likely to provoke clinically important distress today because of improvements in prognosis, treatment, patient support, and reduced stigma [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available data indicate that cancer-related distress generally diminishes with time after diagnosis [10,[30][31][32], increasing again after a possible recurrence [33,34].…”
Section: Introductionmentioning
confidence: 99%